ANALISIS HUKUM AURAT PRIA - Agus Syihabudin (Fakultas Seni Rupa dan Desain ITB, 2011)
Humans have a civilization (civilization) that distinguishes it from animal creatures. With this civilization, humans appear to be caliph (leader) on earth. One of the human civilization is the dress code. Dressed according to Islamic teaching ethics does not simply include appropriate and inappropriate, but set a mandatory closed genitalia from view of others and relate to legal requirements worship prayers. The study of male genitalia are closely related to the objective conditions of Indonesian society that tends to get dressed without closing the thigh as when exercising. In fact, most people in West Irian until today there are those who wear koteka, ie clothing that simply closes the groin and anus. Conceivably, if the thigh assessed male genitalia, then males wearing shorts forbidden by the legal status of